On the statistical analysis of biomechanical arms - Galhano, Alexandra (2019)
Standard joint-actuated manipulators have poor performances due to the high requirements imposed by the transients of the operational tasks. Muscle-actuated arms are superior because the anatomic levers adapt the manipulating requirements to the actuators. The statistical analysis of thes systems highlights its main properties and cosntitutes a step towards the design of new mechanical robotic structures, with performances closer to the biological arms.